Comparison of biomechanical parameters of two Chinese cervical spine rotation manipulations based on motion capture and finite element analysis - Lin, Dongxin; He, Zaopeng; Weng, Rui; Zhu, Yuhua; Lin, Zhiwei; Deng, Yuping; Yang, Yang; Tan, Jinchuan; Wang, Mian; Li, Yanbin; Huang, Gang; Yu, Guanghao; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Objective： The purpose of this study was to obtain the stress-strain of the cervical spine structure during the simulated manipulation of the oblique pulling manipulation and the cervical rotationtraction manipulation in order to compare the mechanical mechanism of the two manipulations. Methods：A motion capture system was used to record the key kinematic parameters of operating the two manipulations. At the same time, a three-dimensional finite element model of the C0-T1 full healthy cervical spine was established, and the key kinematic parameters were loaded onto the finite element model in steps to analyze and simulate the detailed process of the operation of the two manipulations.Results ： A detailed finite element model of the whole cervical spine including spinal nerve roots was established, and the validity of this 3D finite element model was verified. During the stepwise simulation of the two cervical spine rotation manipulations to the right, the disc (including the annulus fibrosus and nucleus pulposus) and facet joints stresses and displacements were greater in the oblique pulling manipulation group than in the cervical rotation-traction manipulation group, while the spinal cord and nerve root stresses were greater in the cervical rotation-traction manipulation group than in the oblique pulling manipulation group. The spinal cord and nerve root stresses in the cervical rotation-traction manipulation group were mainly concentrated in the C4/5 and C5/6 segments.Conclusion：The oblique pulling manipulation may be more appropriate for the treatment of cervical spondylotic radiculopathy, while cervical rotation-traction manipulation is more appropriate for the treatment of cervical spondylosis of cervical type. Clinicians should select cervical rotation manipulations for different types of cervical spondylosis according to the patient's symptoms and needs.